Using Cultivation Theory to Analyze the Impact of Different Media on Public Perception of Urban Forests as Climate Change Solution - Rahim Maleknia; Reza Azizi; Mohammad Reza Pakravan Chavardeh (Sustainable Earth Trends)
Urban trees and forests play a critical role in mitigating climate change by enhancing ecological and social resilience in cities. Despite their importance, public understanding of their benefits for combating climate change and the role of the media in shaping these perceptions remains underexplored. This study addressed this research gap by examining how different media platforms influence citizens' perceptions of urban forests' contributions to climate change mitigation. Using cultivation theory as a framework, the study aimed to assess the impact of various media channels, including social media, television, print media, and blogs, on public perceptions. A quantitative research design was employed, with data collected through a structured online survey administered to 410 urban residents. Structural equation modeling was used to analyze the relationships between media exposure and citizens' perceptions. The findings reveal that social media and television are the most influential in shaping public perceptions, while traditional media forms such as print and blogs show no significant impact. Social media, in particular, emerged as the most effective platform, likely due to its interactive and immediate nature, while television remains relevant due to its visual appeal and broad reach. These results have important implications for environmental communication strategies, suggesting that policymakers should prioritize social media and television campaigns to effectively engage citizens and promote urban forest conservation. By understanding and leveraging these influential platforms, authorities can enhance public perceptions and support for sustainable urban development and climate resilience initiatives.